INTORNO AL MONDO IN CINQUANT’ANNI: VIAGGIO ALLA MANIERA DI ULISSE ATTRAVERSO LA POESIA DI HÉDI BOURAOUI (1966-2016) - , Elizabeth Sabiston, Trans. M. Selvaggio (Revue CMC Review, 2017)
This is a review article on Transpoétiquement vôtre. Anthologie (1966-2016) / Transpoeticamente vostro. Antologia (1966-2016), a selection of Hédi Bouraoui’s poetry over 50 years, edited and translated into Italian by Mario Selvaggio, who also provides the Introduction. Hédi Bouraoui has written an Avant-Propos looking back over a long writing career. The article compares his career to a Ulyssean voyage, and sees him as a Nomad of language, of cultures, of Otherness. This article has also been translated into French and Italian (see below).